Islam in Turkish cinema - Yorulmaz, Bilal; Blizek, William L. (My University, 2014)
This essay describes the history of Turkish cinema from its origins in 1896 until the present, focusing upon how Islam and religious Muslims are portrayed in the movies. For historical, political, and cultural reasons, Islam and religious Muslims have often been portrayed in a negative light, even though Turkey is a predominantly Muslim country. Present day Turkish cinema offers a more eclectic array of movies, including movies that show Islamic practices in daily life and movies that portray Islam in a favorable light.
Keywords: Islam, Muslims, Yesilçam Cinema, Milli Cinema, Marxist Cinema, Religious Education